ASSESSMENT DETERMINATION OF FATIGUE CRITERIA BASED ON THE SUSTAINED ATTENTION TEST (SAT) - Za'imah Maznah, Fina
Fatigue is an important issue in transportation accidents. Sleepiness and fatigue cause a person's alertness to decrease. Fatigue is closely related to alertness. The purpose of this study is to develop a score for the fatigue criteria derived from the Sustained Attention Test (SAT). A total of 50 people participated in this study by measuring alertness, levels of sleepiness and fatigue at the time of fit (baseline) and drowsiness. This study used a within subject experiment with measuring instruments in the form of SAT, Karolinska Sleepiness Scale (KSS), and Visual Analogue Scale (VAS). SAT is a tool used to measure alertness. KSS and VAS are subjective measuring tools for measuring the level of sleepiness and fatigue. The statistical tests used in this study are the Mann Whitney U Test, correlation test, logistic regression and Receiver Operating Characteristics (ROC). The value of the fatigue criteria is obtained from the maximum value of the Youden Index. The results showed that the respondent's attention at baseline and drowsiness had a significant difference. The% miss SAT parameter has a strong correlation with KSS and VAS. Based on the results of the fatigue detection model based on ordinal logistic regression and the ROC curve, SAT parameters are recommended for detecting fatigue. The fatigue detection model consists of three levels, namely the alert level, mild fatigue and severe fatigue. Based on the Youden Index method on the% miss SAT parameter, the cut off value for the start of mild fatigue is at 36% and the start of severe fatigue is at 61.5%. This study has limitations in controlling sleep duration and sleep quality of participants who rely on participants' honesty, not using assistive devices. In addition, the measuring instruments for sleepiness and fatigue using subjective measuring instruments, namely KSS and VAS, were not validated by using an objective measuring instrument in the form of an EEG.